All-Door Boarding in San Francisco, California. Issue 1 (January 2015) - Lee, Jason; Papas, David
For generations, the transit industry has had to balance the desire for faster boarding with the need to collect fares. On July 1, 2012, the San Francisco Municipal Transportation Agency (SFMTA) in California addressed this challenge by becoming North America's first multimodal transit operator to implement all-door boarding systemwide. Customers with valid fare media may enter through any door of any vehicle at any time. Unlike other transit providers that used proof of payment, SFMTA still allowed customers to pay cash on board vehicles at surface stops, thus avoiding the expenses associated with wayside ticket vending machines. San Francisco's operating environment provided ideal conditions to demonstrate the potential benefits of all-door boarding. Serving the nation's second-densest major city with crowded transit vehicles largely operating in mixed traffic, SFMTA must make efficient use of every minute in revenue service and cannot afford excessive time at stops. Two years after the policy's implementation, a comprehensive and multi-factor analysis revealed incremental improvements in dwell times and fare compliance. Overall bus speeds increased slightly despite ridership growth and a population and employment boom.